Doubting Thomas: A Defense of Thomas Aquinas' Account of Divine Providence in Response to David Fergusson - Hodson, Nathaniel (Perichoresis, 2025)
This essay constitutes a response to two criticisms of Thomas Aquinas' account of divine providence which David Fergusson puts forward in his book The Providence of God: A Polyphonic Account. I first argue that on Thomas' account, God does not determine good and evil with a "single divine intention" (Ferguson 2018: 73). Instead, God's will and activity are related to good and evil quite asymmetrically. I then argue, against Fergusson, that Thomas' account of divine providence assigns a great role to the special and recognizable work of the Holy Spirit. I conclude by noting that Thomas' account of providence addresses many of Fergusson's own concerns in his constructive project.